Uni-transporter finder4U: enhancing trusted transportation services by harnessing the universities and network-of-mosques (NoM) capabilities - Ahmad Dahlan, Abdul Rahman; Roslan, Muhammad Nasiruddin; Ahmad Hamdany, Irfan Farhan; Syamil Nazir, Muhamad Izzat (Eclat Research Publication, 2017)
This project is made for Universities students in Malaysia to do their transporter business. This Uni-Transporter Finder4U can provide them to gain more customer especially student who live in campus. This project is being done in peninsular of Malaysia. This project use universities and mosques as centre of network for this system. A part of that, people of masjid can volunteer their selves to become a transporter. This project is also made to help poor people and the needy that need any transportation services. In addition the donor can donate their money to help the poor people to get into transporter. With this transporter finder application, people can easy to get transportation service anywhere with the cheap price, trusted driver and comfortable services.